Faktor-Faktor yang Mempengaruhi Konsep Diri Remaja di SMPN 13 Yogyakarta - Gita Kania Saraswatia; Zulpahiyana Zulpahiyana; Siti Arifah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
Self-concept is weak disturbed in adolescent. Self-concept is not formed from hereditas factor, self-consept is formed and developed through experience and relationship with people. Adolescent with positive self-consept have low level of juvenile deliquency. Meanwhile, adolescent with negative self-concept high level of juvenile deliquency. The purpose of this study was to identify factors that influence the self-concept in adolescent. This study was used an observasional with cross sectional design. Samples was obtained by simple stratified random sampling which consisted of 162 people. Analysis was used kendal-tau test and logistic regression test. The results of kendal-tau test showed that there was a significan influence of parenting care (0.000), peer group (p=0.000), physical performance role (p=0.000), self-esteem role (p=0.000) on self-concept of adolescent. The results of logistic regression test showed that variabel with the most influencing to self concept in adolescent was peer group. In conclusion, there was a significant effect of parenting care, peer group, physical performance role and self-esteem role of self-concept adolescent. The factors that most affect self-concept of adolescent is peer group.